Nickel-containing AgZnO electric contact material and preparation method thereof

The nickel-containing ZnO composite powder was prepared by the sol-gel method and the AgZnO electrical contact material was prepared by the repressure and resinterruption molding technology, which solved the contact wear, arc extinguishing and material transfer resistance of AgZnO electrical contact material in application. The poor problem significantly improves the physical and mechanical properties of the material.

CN119491138APending Publication Date: 2025-02-21SHANGLUO UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411717203.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

AgZnO electrical contact materials show a greater tendency to contact wear, poor arc extinguishing and material transfer resistance in applications, which affect the safety and stability of electrical equipment.

Method used

The sol-gel method was used to prepare nickel-containing ZnO composite powders with uniform particle size and good dispersion, and the nickel-containing AgZnO electrical contact material was prepared by repressure and resintercalation molding technology.

Benefits of technology

Through the addition of nickel, the agglomeration phenomenon of ZnO nanopowder in the Ag matrix is ​​significantly improved, the density, conductivity, Vickers hardness and mechanical properties of the material are improved, and the material's resistance to wear and arc resistance is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119491138A_ABST
    Figure CN119491138A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of electric contact materials, and relates to a nickel-containing AgZnO electric contact material and a preparation method thereof. The preparation method of the nickel-containing AgZnO electric contact material comprises the following steps: (1) preparing nickel-containing ZnO composite powder by adopting a sol-gel method; (2) adding Ag powder and the nickel-containing ZnO composite powder into a container, adding a solvent, carrying out ultrasonic mixing, and drying to obtain a mixture; (3) pressing the mixed material obtained in the step (2) into a blank, sintering for the first time in an inert atmosphere, and cooling to room temperature after sintering to obtain a prefabricated material; and (4) carrying out compression molding on the prefabricated material obtained in the step (3) again, carrying out secondary sintering in an inert atmosphere, and cooling to room temperature after sintering to obtain the nickel-containing AgZnO electric contact material. Compared with an AgZnO electric contact material prepared from ZnO, the density, the conductivity and the Vickers hardness of the obtained nickel-containing AgZnO electric contact material are increased by 2.8%, 13.5% and 28.8% respectively.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electric contact materials and relates to a nickel-containing AgZnO electric contact material and a preparation method thereof. Background Art

[0002] As a key functional component of various AC and DC contactors, relays, circuit breakers and transfer switches, electrical contacts are responsible for connecting and disconnecting circuits and carrying working currents. The quality of their performance directly determines the reliability and stability of electrical equipment operation. The rapid development of strategic emerging industries such as new energy power, smart homes, and a new generation of information electronics has put forward increasingly stringent requirements on the performance, reliability and service life of electrical materials. In order to meet the requirements of electrical contacts in applications, electrical contact materials often need to have excellent electrical and thermal conductivity, low contact resistance, high hardness, excellent resistance to arc erosion and mechanical wear, and other properties.

[0003] Over the years, people have developed a variety of AgMeO electrical contact materials, such as AgCdO, AgSnO 2 、AgCuO、AgTiB 2 , AgZnO, etc. Among them, the universal electrical contact material AgCdO can effectively reduce the contact temperature rise and welding phenomenon due to the endothermic decomposition of CdO under high arc temperature, and the arc extinguishing effect of the decomposition product makes the material show excellent electrical contact performance. However, the heavy metal Cd easily produced by AgCdO during service poses potential hazards to the human body and the environment. As a new candidate material to replace AgCdO, AgZnO electrical contact material has low contact resistance, excellent resistance to welding and arc erosion, good breaking performance, short arcing duration, strong resistance to arc burning, and environmental friendliness. It performs well in many applications. However, due to factors such as poor interface wettability between Ag and ZnO, high aggregation degree of ZnO at the Ag / ZnO interface, and poor dispersion of the reinforcement ZnO in the Ag matrix, AgZnO electrical contact material shows a greater tendency to contact wear, poor arc extinguishing and resistance to material transfer, which poses a serious threat to the safety and stability of electrical equipment. Therefore, in order to ensure the safety and stability of the electrical system, improving the performance of AgZnO electrical contact materials is an urgent problem to be solved. Summary of the invention

[0004] The object of the present invention is to provide a nickel-containing AgZnO electrical contact material and a preparation method thereof.

[0005] The implementation process of the present invention is as follows:

[0006] A method for preparing a nickel-containing AgZnO electrical contact material comprises the following steps:

[0007] (1) Preparing nickel-containing ZnO composite powder by sol-gel method;

[0008] (2) adding Ag powder and nickel-containing ZnO composite powder into a container, adding a solvent, performing ultrasonic mixing, and drying to obtain a mixture;

[0009] (3) pressing the mixed material obtained in step (2) into a blank, sintering it for the first time under an inert atmosphere, and cooling it to room temperature after sintering to obtain a prefabricated material;

[0010] (4) Pressing the preform obtained in step (3) into a new shape, sintering it for a second time under an inert atmosphere, and cooling it to room temperature after sintering to obtain a nickel-containing AgZnO electrical contact material.

[0011] Furthermore, in step (2), the mass ratio of Ag powder to nickel-containing ZnO composite powder is (95-94):(5-6), the solvent is ethanol or acetone, and the ultrasonic mixing time is 25-40 minutes.

[0012] Furthermore, in step (3), the pressure for pressing the blank is 280-320 MPa, and the holding time is 280-320 s; the inert gas is nitrogen or argon; the temperature for the first sintering is 880-920° C., and the sintering time is 1.8-2.2 h.

[0013] Furthermore, in step (4), the pressure of the preform for pressing again is 1050-1120 MPa, and the holding time is 280-320 s; the inert gas is nitrogen or argon; the temperature of the second sintering is 580-620° C., and the sintering time is 1.8-2.2 h.

[0014] Further, in step (1), the specific process of preparing the nickel-containing ZnO composite powder by the sol-gel method is as follows:

[0015] (1.1) Dissolving zinc salt and nickel salt in water, adding polyethylene glycol and ammonia water to obtain a precursor solution;

[0016] (1.2) Add glacial acetic acid to the precursor solution under stirring conditions, and vigorously stir in a water bath to obtain a sol solution;

[0017] (1.3) aging the sol solution at room temperature and then drying it to obtain a xerogel;

[0018] (1.4) The dry gel is calcined to obtain nickel-containing ZnO composite powder.

[0019] Furthermore, the zinc salt is selected from zinc acetate or zinc nitrate; the nickel salt is selected from nickel chloride or nickel nitrate.

[0020] Furthermore, the mass ratio of the zinc salt to the nickel salt is (6-7):(0.4-0.55), the mass ratio of the zinc salt to water is (6-7):30, the mass volume ratio of the zinc salt to polyethylene glycol is (6-7) g:(5-7) mL, the mass volume ratio of the zinc salt to aqueous ammonia is (6-7) g:(5-7) mL, and the mass volume ratio of the zinc salt to glacial acetic acid is (6-7) g:50 mL.

[0021] Furthermore, in step (1.2), the water bath temperature is 65 to 75° C.; in step (1.3), the aging time is 23 to 26 hours.

[0022] Furthermore, in step (1.4), the calcination temperature is 480-520° C., the heating rate during the calcination process is 2° C. / min, and the calcination time is 30-60 min.

[0023] The nickel-containing AgZnO electrical contact material obtained by the above preparation method.

[0024] Positive effects of the present invention:

[0025] (1) The present invention adopts a sol-gel method to prepare a nickel-containing ZnO composite powder with uniform particle size and good dispersibility, and prepares a new nickel-containing AgZnO electrical contact material through a double pressing and double firing molding technology.

[0026] (2) The addition of nickel has a significant effect on the dispersion of the electrical contact material powder. Metallic nickel effectively improves the agglomeration of ZnO nanopowder in the Ag matrix.

[0027] (3) Compared with the AgZnO electrical contact material prepared from ZnO, the density, conductivity and Vickers hardness of the AgZnO electrical contact material containing nickel increased by 2.8%, 13.5% and 28.8%, respectively.

[0028] (4) The nickel-containing AgZnO electrical contact material obtained by the present invention has better mechanical properties, and the elastic modulus is increased by 16.04%. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 is the TG-DSC curve of the dry gel in Example 1;

[0030] Figure 2 XRD patterns of ZnO composite powders with different Ni contents, including (a) 0wt.%; (b) 0.5wt.%; (c) 1.0wt.%; (d) 1.5wt.%;

[0031] Figure 3SEM morphologies of ZnO composite powders with different Ni contents, including (a) 0wt.%; (b) 0.5wt.%; (c) 1.0wt.%; (d) 1.5wt.%;

[0032] Figure 4 The SEM and EDS analysis of the ZnO composite powder containing 0.5 wt.% nickel obtained in Example 1, wherein (a) SEM, (b) Ni, (c) O, (d) Zn;

[0033] Figure 5 for Figure 4 (a) Element content analysis diagram of area A;

[0034] Figure 6 The XPS spectra of the ZnO composite powder containing 0.5 wt.% nickel obtained in Example 1, including (a) XPS total spectrum, (b) Ni2p spectrum, (c) Zn2p spectrum, and (d) O1s spectrum;

[0035] Figure 7 The microstructure morphology of the nickel-containing AgZnO electrical contact material obtained in Example 1, wherein (a) the experimental blank sample AgZnO material, (b) the nickel-containing AgZnO electrical contact material;

[0036] Figure 8 The effect of adding nickel metal on the physical properties of AgZnO electrical contact materials;

[0037] Fig. 9 The fracture morphology of the nickel-containing AgZnO electrical contact material obtained in Example 1, wherein (a) is the experimental blank sample AgZnO material, and (b) is the nickel-containing AgZnO electrical contact material. DETAILED DESCRIPTION

[0038] The present invention will be further described below in conjunction with the embodiments.

[0039] The method for preparing the nickel-containing AgZnO electrical contact material of the present invention comprises the following steps:

[0040] (1) Preparing nickel-containing ZnO composite powder by sol-gel method;

[0041] (1.1) Dissolve a zinc salt and a nickel salt in water, add polyethylene glycol and ammonia water to obtain a precursor solution; the zinc salt is selected from zinc acetate or zinc nitrate; the nickel salt is selected from nickel chloride or nickel nitrate. The mass ratio of the zinc salt to the nickel salt is (6-7):(0.4-0.55), the mass ratio of the zinc salt to water is (6-7):30, the mass volume ratio of the zinc salt to polyethylene glycol is (6-7) g:(5-7) mL, and the mass volume ratio of the zinc salt to ammonia water is (6-7) g:(5-7) mL.

[0042] (1.2) Under stirring conditions, glacial acetic acid is added to the precursor solution, and the mixture is vigorously stirred in a water bath at 65 to 75° C. to obtain a sol solution; the mass volume ratio of the zinc salt to the glacial acetic acid is (6 to 7) g:50 mL.

[0043] (1.3) aging the sol solution at room temperature for 23 to 26 hours and then drying to obtain a xerogel;

[0044] (1.4) The dry gel was calcined at 480-520°C for 30-60 min to obtain nickel-containing ZnO composite powder. The heating rate during the calcination process was 2°C / min.

[0045] (2) Add Ag powder and nickel-containing ZnO composite powder into a container, add ethanol or acetone solvent, perform ultrasonic mixing for 25 to 40 minutes, and dry to obtain a mixture; the mass ratio of Ag powder to nickel-containing ZnO composite powder is (95 to 94): (5 to 6). There is no limit on the amount of ethanol or acetone solvent added in this step, as long as the amount of solvent added can submerge the solid amount and achieve mixing.

[0046] (3) The mixed material obtained in step (2) is pressed into a blank at a pressure of 280 to 320 MPa and a holding time of 280 to 320 seconds; the blank is first sintered at 880 to 920° C. for 1.8 to 2.2 hours in a nitrogen or argon atmosphere, and then cooled to room temperature to obtain a preform.

[0047] (4) Pressing the preform obtained in step (3) again into shape, the pressure of the preform pressed again into shape is 1050-1120 MPa, and the holding time is 280-320 s; sintering for a second time at 580-620° C. for 1.8-2.2 h in a nitrogen or argon atmosphere, and cooling to room temperature after sintering to obtain a nickel-containing AgZnO electrical contact material.

[0048] The tablet press used in the method of the present invention is a FYS-30F desktop powder tablet press produced by Tianjin Sichuang Jingshi Technology Development Co., Ltd., and the tubular furnace is a NBD-O1200 tubular furnace produced by Henan Nobadi Material Technology Co., Ltd.

[0049] Example 1

[0050] The method for preparing the nickel-containing AgZnO electrical contact material described in this embodiment comprises the following steps:

[0051] (1) Preparing nickel-containing ZnO composite powder by sol-gel method;

[0052] (1.1) Weigh 6.6 000 g of Zn(CH 3 COO 2 ·2H 2O was fully dissolved in 30 mL of deionized water, and 0.4956 g of NiCl 2 6H 2 O, stir to dissolve completely; then add 6 mL of polyethylene glycol 400, and then add 6 mL of 25% NH 3 ·H 2 O solution to obtain a precursor solution;

[0053] (1.2) Place the precursor solution in a heat-collecting constant temperature heating magnetic stirrer. Under stirring conditions, add 50 mL of C 2 H 5 OH solution, stirred vigorously in a constant temperature water bath at 70 °C for 2 h, to obtain a blue transparent sol solution;

[0054] (1.3) The sol solution was aged at room temperature for 24 h, and then transferred to an oven and dried at 60°C to obtain a xerogel;

[0055] (1.4) The dry gel was placed in a tubular furnace and slowly heated to 500°C at a rate of 2°C / min, kept at that temperature for 50 min, and cooled to room temperature along with the furnace to obtain a ZnO composite powder containing 0.5 wt.% nickel.

[0056] (2) 94.5 wt.% of Ag powder and 5.5 wt.% of nickel-containing ZnO composite powder were added to a beaker, and ethanol solvent was added, and ultrasonic mixing was performed for 30 minutes. A magnet was then added and stirring was continued on a magnetic stirrer until the anhydrous ethanol was completely evaporated. The mixture was then completely dried in an oven at 60°C to obtain a mixture.

[0057] (3) using a Φ10 stainless steel mold to press the mixed material obtained in step (2) into a blank on a desktop powder tablet press, with a pressing force of 300 MPa and a holding time of 300 s; placing the pressed blank into a covered corundum crucible, placing it in a tubular furnace, and sintering it at 900 °C for a first time for 2 h under a nitrogen atmosphere at a heating rate of 5 °C / min. After sintering, cooling it to room temperature to obtain a preform.

[0058] (4) The preform obtained in step (3) is pressed again at a pressure of 1100 MPa and a holding time of 300 s; the preform is sintered for a second time at 600° C. for 2 h in a nitrogen atmosphere, and cooled to room temperature after sintering to obtain a nickel-containing AgZnO electrical contact material.

[0059] Experimental blank sample: The preparation method and parameters are the same as step (1) in Example 1, except that no NiCl is added 2 6H 2O, and ZnO powder was prepared as a blank sample of the experimental ZnO composite powder containing nickel. The obtained ZnO powder was subjected to the same preparation method and parameters as steps (2) to (4) in Example 1 to prepare AgZnO material.

[0060] Comparative Example 1: The preparation method and parameters are the same as step (1) in Example 1, except that: NiCl 2 6H 2 The added amount of O was 0.9912 g, and finally a ZnO composite powder containing 1.0 wt.% nickel was prepared.

[0061] Comparative Example 2: The preparation method and parameters are the same as step (1) in Example 1, except that: NiCl 2 6H 2 The added amount of O was 1.4868 g, and finally a ZnO composite powder containing 1.5 wt.% nickel was prepared.

[0062] Performance Test:

[0063] (1) The tests and instruments involved are as follows:

[0064] The phase composition of powder and bulk materials was analyzed by X-ray diffractometer (PaNalytical, the Netherlands). The thermal decomposition of zinc gel was analyzed by STA449F3 synchronous thermal analyzer (NETZSCH, Germany). The morphology of powder and electrical contact materials was observed by DMI3000 M metallographic microscope (Leica Instruments Co., Ltd.) and SEM 3200 scanning electron microscope (Guoyi Quantum Technology Co., Ltd.). The element distribution of bulk materials was analyzed by EDS. The chemical valence state of powder was analyzed by X-ray photoelectron spectrometer (Thermo Fisher Scientific, USA). The conductivity of bulk materials was tested by Sigma 2008C digital eddy current metal conductivity meter (Xiamen Tianyan Instrument Co., Ltd.), Vickers hardness was tested by HV-1000TPTA microhardness tester (Laizhou Weiyi Testing Equipment Manufacturing Co., Ltd.), and compression performance of materials was tested by WDW-50 microcomputer-controlled electronic universal testing machine (Jinan Hengruijin Testing Machine Co., Ltd.).

[0065] (2) Test results analysis

[0066] (2.1) TG-DSC analysis of the dry gel in Example 1

[0067] Figure 1The TG-DSC curve of the dry gel in Example 1 is shown in the figure. It can be seen from the figure that within the experimental temperature range, the TG curve of the sample mainly shows two stages of mass reduction process. In the first stage, in the range of 30-125°C, the sample weight loss rate is about 7.96%, which should be that the sample absorbs heat for water evaporation; in the second stage, in the range of 125-475°C, the sample weight loss rate is about 73.99%, accompanied by an obvious endothermic process, which should be that Zn(CH 3 COO 2 Thermal decomposition into ZnO, the sample mass does not change after 500℃. Therefore, the calcination temperature of the powder is determined to be 500℃ to ensure its complete reaction.

[0068] (2.2) Phase analysis of nickel-containing ZnO composite powder

[0069] The calcined ZnO powder and the nickel-containing ZnO composite powder were subjected to XRD test analysis. The analysis results are as follows: Figure 2 As shown. The diffraction peaks with 2θ of 44.6°, 51.9°, and 76.4° correspond to the diffraction peaks of Ni (JCPDS No.00-004-0850), and the remaining diffraction peaks are all attributed to ZnO (JCPDS No.01-079-0207), without other impurity peaks. This indicates that the ZnO powder prepared by the sol-gel method has only ZnO phase, and the prepared nickel-containing ZnO composite powder is composed of ZnO phase and nickel phase, and with the increase of the amount of metallic nickel added, the intensity of the diffraction peak of nickel is also significantly enhanced.

[0070] (2.3) SEM morphology analysis of nickel-containing AgZnO electrical contact materials

[0071] Figure 3 The SEM microstructure of ZnO composite powders containing different amounts of nickel is shown, which clearly reveals the dispersion state and particle size of the added metallic nickel in the ZnO matrix.

[0072] Depend on Figure 3 (a) It can be seen that the ZnO powder was prepared by the sol-gel method. Due to the large surface energy, the ZnO powder showed serious aggregation and appeared fluffy. Figure 3 (b) shows the microstructure of ZnO composite powder containing 0.5wt.% nickel. It can be clearly seen from the figure that the particle size of ZnO powder has increased significantly, approaching the micron level; nickel is evenly embedded in the ZnO micron powder to form a dense coral shape. Nickel significantly increases the particle size of ZnO and improves the distribution state of ZnO powder. The ZnO composite powder containing 0.5wt.% nickel shows good dispersibility, no obvious agglomeration phenomenon, and the particle size is moderate and evenly distributed. Figure 3As shown in (c), in the ZnO composite powder containing 1.0wt.% nickel, the metal Ni particles are relatively large, with a diameter of about 5μm, and are prone to agglomeration. This shows that the increase in nickel source concentration leads to a significant increase in nickel particle size. When the nickel addition amount increases to 1.5wt.%, the nickel particles show obvious adhesion, and the particle distribution appears chaotic and irregular. The dispersibility of nickel and ZnO powders is extremely poor, as shown in Figure 2. Figure 3 From the above analysis, when the nickel addition amount is 0.5wt.%, the nickel-containing ZnO composite powder with uniform particle size and good dispersibility is obtained by the sol-gel method.

[0073] (2.4) EDS analysis of ZnO composite powder containing 0.5 wt.% nickel

[0074] Figure 4 The SEM morphology and EDS surface scanning analysis diagram of ZnO composite powder containing 0.5wt.% nickel. Figure 4 The surface scanning of area A in (a) obtained the distribution images of Ni, O and Zn elements as shown in the figure. Figure 4 As shown in (b), (c) and (d). Figure 4 The number and distribution of green dots in (b) characterize the distribution of metal Ni on the surface of ZnO powder and the doping effect. As can be seen from the figure, the Ni element is distributed evenly on the ZnO surface, the particle size is moderate, and there is no obvious agglomeration phenomenon. Figure 4 (c) and Figure 4 (d) shows that the element distribution of Zn and O is similar, and both show higher content in region A. This indicates that region A is composed of Zn, O and a small amount of Ni, and the Ni element is dispersed in the ZnO reinforcement.

[0075] Figure 5 yes Figure 4 The element content analysis of region A in (a) shows that the prepared ZnO composite powder is mainly composed of Zn and O elements, and the atomic ratio of Zn:O is close to 1:1, indicating that the composite powder is mainly ZnO powder. In addition, the mass fraction of Ni element in the composite powder is 0.68wt.%, which is close to the target doping ratio of 0.5wt.%, proving that the present invention successfully prepared ZnO composite powder containing 0.5wt.% nickel by sol-gel method.

[0076] (2.5) XPS analysis of ZnO composite powder containing 0.5 wt.% Ni

[0077] To further confirm the phase analysis results of ZnO composite powder containing 0.5wt.% nickel, the chemical state of the composite powder was analyzed by X-ray photoelectron spectroscopy (XPS), and the binding energy in the XPS spectrum was calibrated with C1s (284.8ev), and the peak fitting was performed. The XPS test results of ZnO composite powder containing 0.5wt.% nickel are shown in Figure 2. Figure 6 shown. Figure 6 (a) shows that the sample is composed of three elements: Zn, Ni, and O, which is consistent with the results of XRD and EDS. The XPS spectrum of Ni2p is shown in Figure 6 As shown in (b), Ni2p consists of two peaks (Ni2p3 / 2 and Ni2p1 / 2), where the binding energy and spin-orbit splitting of the double peaks at 852.58 eV and 870.38 eV are 17.8 eV (ΔNi metal = 17.3 eV), which directly confirms the presence of the Ni element and emphasizes that the main element doped into the ZnO composite powder is metallic Ni. Figure 6 (c) is the energy level spectrum of Zn 2p. The characteristic peaks at 1021.18 eV and 1043.98 eV in the figure correspond to the Zn2p3 / 2 and Zn2p1 / 2 core energy levels of ZnO. The binding energy difference between the two peaks is 22.8 eV, which confirms the existence of Zn 2 +[14,15] .like Figure 6 As shown in (d), the O1s peak at about 530.08 eV is attributed to oxygen in the ZnO lattice. Therefore, it is confirmed that the ZnO composite powder containing 0.5 wt.% nickel is composed of metal Ni and ZnO.

[0078] (2.6) Effect of nickel addition on the structure of AgZnO electrical contact materials

[0079] The microstructure of AgZnO electrical contact materials containing nickel is as follows Figure 7 As shown in the figure. The dark gray is the ZnO enhanced phase, and the light gray is the Ag phase. Figure 7 (a) It can be seen that in the morphology of the AgZnO electrical contact material prepared from ZnO powder, the ZnO particles are large in size and irregular in shape, with a chaotic overall distribution. The agglomeration of ZnO powder leads to uneven distribution in the Ag matrix, and the aggregation phenomenon is more obvious. When 0.5wt.% of metallic nickel is added, the particles in the nickel-containing AgZnO electrical contact material become significantly smaller, the shape tends to be more round, and the agglomeration phenomenon of ZnO in the Ag matrix is ​​significantly improved. This shows that the addition of metallic nickel can improve the dispersibility of ZnO particles, making the reinforcement phase more evenly distributed in the matrix material, thereby improving the performance of the material.

[0080] (2.7) Effect of nickel addition on the physical properties of AgZnO electrical contact materials

[0081] Figure 8The physical properties of the nickel-containing AgZnO electrical contact material prepared from the nickel-containing ZnO composite powder. As can be seen from the figure, the density, conductivity and Vickers hardness of the nickel-containing AgZnO electrical contact material are 94.59%, 60.76% IACS and 67.9HV, respectively, which are 2.8%, 13.5% and 28.8% higher than those of the AgZnO electrical contact material prepared from ZnO powder. Metallic nickel significantly increases the physical properties of the AgZnO electrical contact material.

[0082] (2.8) Effect of nickel addition on the mechanical properties of AgZnO electrical contact materials

[0083] Fig. 9 This is the compression fracture morphology of the nickel-containing AgZnO electrical contact material. Fig. 9 (a) It can be seen that in the fracture morphology of the AgZnO electrical contact material prepared from ZnO powder, there are long and deep cracks formed along the Ag grain boundary, such as Fig. 9 (a) Red dotted line. This shows that the interface bonding strength of Ag / ZnO is very poor, which is the fundamental reason for the poor mechanical properties of AgZnO electrical contact materials. Fig. 9 (b) It can be seen that there are no large cracks on the fracture surface of the nickel-containing AgZnO electrical contact material, and traces of Ag grain tearing are observed in the local enlarged image, indicating that the introduction of nickel enhances the interface bonding strength of Ag / ZnO and transfers the tearing surface to the interior of the grain, thereby increasing the mechanical properties of the nickel-containing AgZnO electrical contact material. In addition, compared with the AgZnO electrical contact material prepared from ZnO powder, the elastic modulus of the nickel-containing AgZnO electrical contact material increased by 16.04%, and the addition of nickel significantly increased the Young's elastic modulus of the nickel-containing AgZnO electrical contact material.

[0084] Example 2

[0085] The method for preparing the nickel-containing AgZnO electrical contact material described in this embodiment comprises the following steps:

[0086] (1) Preparing nickel-containing ZnO composite powder by sol-gel method;

[0087] (1.1) Weigh 6.0 000 g of Zn(NO 3 ) 2 6H 2 O was fully dissolved in 30 mL of deionized water, and 0.4000 g of Ni(NO 3 ) 2 6H 2 O, stir to dissolve completely; then add 5 mL of polyethylene glycol 400, and then add 5 mL of 25% NH 3 ·H 2O solution to obtain a precursor solution;

[0088] (1.2) Place the precursor solution in a heat-collecting constant temperature heating magnetic stirrer. Under stirring conditions, add 50 mL of C 2 H 5 OH solution, stirred vigorously in a constant temperature water bath at 65 °C for 2.5 h to obtain a blue transparent sol solution;

[0089] (1.3) After aging the sol solution at room temperature for 23 h, it was transferred to an oven and dried at 60°C to obtain a xerogel;

[0090] (1.4) The dry gel was placed in a tubular furnace and slowly heated to 480°C at a rate of 2°C / min, kept at that temperature for 30 min, and cooled to room temperature in the furnace to obtain nickel-containing ZnO composite powder.

[0091] (2) 95 wt.% of Ag powder and 5 wt.% of nickel-containing ZnO composite powder were added to a beaker, and ethanol solvent was added, and ultrasonic mixing was performed for 25 minutes. A magnet was then added and stirring was continued on a magnetic stirrer until the anhydrous ethanol was completely evaporated. The mixture was then completely dried in an oven at 70°C to obtain a mixture.

[0092] (3) The mixed material obtained in step (2) is pressed into a blank on a desktop powder tablet press using a Φ10 stainless steel mold, with a pressing force of 280 MPa and a holding time of 320 s; the pressed blank is placed in a covered corundum crucible, which is then placed in a tubular furnace, and sintered for the first time at 920° C. for 1.8 h under an argon atmosphere at a heating rate of 5° C. / min. After sintering, the blank is cooled to room temperature to obtain a preform.

[0093] (4) The preform obtained in step (3) is pressed again at a pressure of 1120 MPa and a holding time of 280 s; the preform is sintered for a second time at 580° C. for 2.2 h in an argon atmosphere, and cooled to room temperature after sintering to obtain a nickel-containing AgZnO electrical contact material.

[0094] Example 3

[0095] The method for preparing the nickel-containing AgZnO electrical contact material described in this embodiment comprises the following steps:

[0096] (1) Preparing nickel-containing ZnO composite powder by sol-gel method;

[0097] (1.1) Weigh 7.0 000 g of Zn(CH 3 COO 2 ·2H 2 O was fully dissolved in 30 mL of deionized water, and 0.55 g of NiCl 2 6H2 O, stir to dissolve completely; then add 7 mL of polyethylene glycol 400, and then add 7 mL of 25% NH 3 ·H 2 O solution to obtain a precursor solution;

[0098] (1.2) Place the precursor solution in a heat-collecting constant temperature heating magnetic stirrer. Under stirring conditions, add 50 mL of C 2 H 5 OH solution, stirred vigorously in a constant temperature water bath at 75 °C for 3 h to obtain a blue transparent sol solution;

[0099] (1.3) After aging the sol solution at room temperature for 26 h, it was transferred to an oven and dried at 70°C to obtain a xerogel;

[0100] (1.4) The dry gel was placed in a tubular furnace and slowly heated to 520°C at a rate of 2°C / min, kept at that temperature for 60 min, and cooled to room temperature in the furnace to obtain nickel-containing ZnO composite powder.

[0101] (2) 94 wt.% of Ag powder and 6 wt.% of nickel-containing ZnO composite powder were added to a beaker, and acetone solvent was added, and ultrasonic mixing was performed for 40 minutes. A magnet was then added and the mixture was continuously stirred on a magnetic stirrer until the acetone was completely evaporated. The mixture was then completely dried in an oven at 60°C to obtain a mixture.

[0102] (3) The mixed material obtained in step (2) is pressed into a blank on a desktop powder tablet press using a Φ10 stainless steel mold, with a pressing force of 320 MPa and a holding time of 280 s; the pressed blank is placed in a covered corundum crucible, which is then placed in a tubular furnace, and sintered for the first time at 880°C for 2.2 h under a nitrogen atmosphere at a heating rate of 5°C / min. After sintering, the blank is cooled to room temperature to obtain a preform.

[0103] (4) The preform obtained in step (3) is pressed again at a pressure of 1050 MPa and a holding time of 320 s; the preform is sintered for a second time at 620° C. for 1.8 h in a nitrogen atmosphere, and cooled to room temperature after sintering to obtain a nickel-containing AgZnO electrical contact material.

[0104] The above contents are further detailed descriptions of the present invention in combination with specific preferred embodiments, and the specific implementation of the present invention cannot be limited to these descriptions. For ordinary technicians in the field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, which should be regarded as falling within the protection scope of the present invention.

Claims

1. A method for preparing a nickel-containing AgZnO electrical contact material, characterized in that: The steps include: (1) Preparing nickel-containing ZnO composite powder by sol-gel method; (2) adding Ag powder and nickel-containing ZnO composite powder into a container, adding a solvent, performing ultrasonic mixing, and drying to obtain a mixture; (3) pressing the mixed material obtained in step (2) into a blank, sintering it for the first time under an inert atmosphere, and cooling it to room temperature after sintering to obtain a prefabricated material; (4) Pressing the preform obtained in step (3) into a new shape, sintering it for a second time under an inert atmosphere, and cooling it to room temperature after sintering to obtain a nickel-containing AgZnO electrical contact material.

2. The method for preparing the nickel-containing AgZnO electrical contact material according to claim 1, characterized in that: In step (2), the mass ratio of Ag powder to nickel-containing ZnO composite powder is (95-94):(5-6), the solvent is ethanol or acetone, and the ultrasonic mixing time is 25-40 minutes.

3. The method for preparing the nickel-containing AgZnO electrical contact material according to claim 1, characterized in that: In step (3), the pressure for pressing the blank is 280-320 MPa, and the holding time is 280-320 s; the inert gas is nitrogen or argon; the temperature for the first sintering is 880-920° C., and the sintering time is 1.8-2.2 h.

4. The method for preparing the nickel-containing AgZnO electrical contact material according to claim 1, characterized in that: In step (4), the pressure of the preform for pressing again is 1050-1120 MPa, and the holding time is 280-320 s; the inert gas is nitrogen or argon; the temperature of the second sintering is 580-620° C., and the sintering time is 1.8-2.2 h.

5. The method for preparing the nickel-containing AgZnO electrical contact material according to claim 1, characterized in that: In step (1), the sol-gel method is used to prepare the nickel-containing ZnO composite powder. (1.1) Dissolving zinc salt and nickel salt in water, adding polyethylene glycol and ammonia water to obtain a precursor solution; (1.2) Add glacial acetic acid to the precursor solution under stirring conditions, and vigorously stir in a water bath to obtain a sol solution; (1.3) aging the sol solution at room temperature and then drying it to obtain a xerogel; (1.4) The dry gel is calcined to obtain nickel-containing ZnO composite powder.

6. The method for preparing the nickel-containing AgZnO electrical contact material according to claim 5, characterized in that: The zinc salt is selected from zinc acetate or zinc nitrate; the nickel salt is selected from nickel chloride or nickel nitrate.

7. The method for preparing the nickel-containing AgZnO electrical contact material according to claim 5, characterized in that: The mass ratio of the zinc salt to the nickel salt is (6-7):(0.4-0.55), the mass ratio of the zinc salt to water is (6-7):30, the mass volume ratio of the zinc salt to polyethylene glycol is (6-7) g:(5-7) mL, the mass volume ratio of the zinc salt to aqueous ammonia is (6-7) g:(5-7) mL, and the mass volume ratio of the zinc salt to glacial acetic acid is (6-7) g:50 mL.

8. The method for preparing the nickel-containing AgZnO electrical contact material according to claim 5, characterized in that: In step (1.2), the water bath temperature is 65 to 75° C.; in step (1.3), the aging time is 23 to 26 hours.

9. The method for preparing the nickel-containing AgZnO electrical contact material according to claim 5, characterized in that: In step (1.4), the calcination temperature is 480-520° C., the heating rate during the calcination process is 2° C. / min, and the calcination time is 30-60 min.

10. The nickel-containing AgZnO electrical contact material obtained by the preparation method according to any one of claims 1 to 9.